Coming of Age: Stressing the importance of threat models. - Zanero, Stefano (Communications of the ACM, 2023)
The article describes the author's experiences in the field of computer security research, noting that many of his colleagues entered the field from a hacking background due to the limited academic resources at the time. He describes the thrill of offensive security research, which focuses on finding vulnerabilities and proposing mitigations, and highlights the fact that security evaluations often revolve around resilience to attacks and that offense-driven thinking is central to security defense. However, the author acknowledges that while this mindset is exciting, it falls short in teaching the public to think sensibly about security issues. He emphasizes the use of threat modeling as the key to effective security, since it involves understanding realistic threats and attack surfaces of systems. Despite the fascination with hacking, the author suggests that the cybersecurity community needs to communicate and prioritize defense, address vulnerabilities in context, and collaborate across disciplines to ensure resilient systems and a safer society.